Fusarium Head Blight of Cultivated and Natural Wild Rice (Zizania palustris) in Minnesota Caused by Fusarium graminearum and Associated Fusarium spp - Nyvall, R F (Plant disease, 1999)
Symptoms of Fusarium head blight on diseased wild rice seed from both cultivated fields and natural stands are shrunken, light weight seeds discolored light tan to light brown with infrequent light pink due to mycelial growth of Fusarium spp. F. graminearum was the predominant species isolated from whole seed at all growth stages, and from shattered seed gathered from four fields in 1994 to 1995. F. anthophilum and F. subglutinans were also frequently isolated at most growth stages, whereas F. acuminatum, F. culmorum, F. solani, and F. semitectum were infrequently isolated at one or more growth stages, and F. camptoceras was isolated only from shattered seed. F. graminearum was the only species isolated from processed seed, although rarely. Fusarium spp. were isolated at the highest percentage from shattered seed. The highest percentage of total Fusarium spp. isolated during seed development was at the milk and dough stages in a cultivated field and at the milk stage in a natural stand; the percentage then declined until the ripe stage in seed from both sites. There were no significant differences in the percentages of Fusarium spp. isolated at growth stages between seed from the cultivated field and from the natural stand. Fusarium spp. were isolated most frequently from whole seed grown in three cultivated fields, compared with the palea and lemma, and caryopsis. F. graminearum and F. anthophilum were frequently isolated from whole seed and all seed structures, whereas F. culmorum and F. sporotrichioides were isolated only from whole seed, F. moniliforme from whole seed, palea and lemma, and caryopsis, and F. subglutinans from whole seed and the palea and lemma only. Deoxynivalenol and nivalenol were identified in three isolates of F. graminearum; however, none of the seed samples from which the isolates were obtained yielded either mycotoxin. Survival of Fusarium spp. in diseased seed was similar from both cultivated and natural sources and occurs in whole seed not immersed in water but not in seed immersed in water.Survival was better in seed stored at 4°C than at -20°C. F. graminearum was reisolated from 81% of seed from inoculated plants but not from seed of noninoculated plants. Pathogenicity of other Fusarium spp. remains to be demonstrated